The Perceptions and Determinants of Auditing and Reporting Quality in the Asia‐Pacific Region. Issue 3 (23rd March 2018) - Boolaky, Pran K.; Soobaroyen, Teerooven; Quick, Reiner
Abstract: A country's institutional environment significantly influences perceptions of auditing and reporting quality (ARQ) at the national level. Relying on a relatively unique measure of ARQ, collated by the World Economic Forum, we evaluate the influence of nine key isomorphic pressures on the ARQ in 26 Asia‐Pacific countries. The results suggest that six of these (the efficacy of the corporate board, securities exchange regulations, reliance on professional management, protection of minority interests, adoption of international financial reporting and prevalence of foreign ownership) have a highly significant influence on the perception of ARQ whereas adoption of international standards on auditing is only moderately significant. However, contrary to expectations, our findings do not support the argument that the efficiency of legal frameworks and political systems significantly influences the perceptions of auditing and reporting quality in the Asia‐Pacific region. These results should be of use to investors and the accounting profession in evaluating economic environments. Abstract : This paper evaluates the influence of nine key isomorphic pressures on auditing and reporting quality (ARQ) in 26 Asia‐Pacific countries. Results suggest that six of these (the efficacy of the corporate board, securities exchange regulations, reliance on professional management, protection of minority interests, adoption of international financial reporting and prevalence of foreign ownership) have a highly significant influence on the perception of ARQ whereas adoption of international standards on auditing is only moderately significant.